Hierarchical level oF managersâ abilities: A Moderator between Quality Management Practices and Company Financial Performance - Ciptono, Wakhid Slamet (Gadjah Mada International Journal of Business, 2007)
This study investigates the moderating impacts of hierarchical level of managersâ abilities on the form and strength of all structural relationships between quality management practices and company financial performance. This study describes the structural relationships among the research constructs âsix critical factors of quality management practices (quality improvement program, supervisory leadership, supplier involvement, management commitment, training to improve products/services, cross-functional relationships); the contextual factors of oil and gas companiesâworld-class performance in operations (world-class company practices, operational excellence practices, company non-financial performance); and company financial performance. It uses a sample of 1,332 managers in 140 strategic business units (SBUs) within 49 oil and gas companies operating in Indonesia. The empirical results indicate that the goodness-of-fit of the unconstrained model is much better than that of the constrained model, and this is an indicator that hierarchical level of managersâ abilities moderates all structural relationships among the research constructs. Hence, the hierarchical level of managersâ abilities acts as a moderating variable of the whole model (i.e., among critical factors of quality management practices, world-class company practices, operational excellence practices, company non-financial performance, and company financial performance). It means that the major contribution of the hierarchical level of managersâ abilities is how to make changes in the organizational system. Top level managersâ abilities are deemed the most capable of making significant changes because of their broad sources of power and influence. Conversely, lower level managersâ abilities find it more difficult making significant changes in the system because of bureaucratic control processes that limit their actions âpowerlessness or a chronic lack of autonomy. Compared to the hierarchical level of managersâ abilities, the degree of autonomy may be a more comprehensive contribution in reference to managersâ abilities to influence an organizational system. Autonomy may not only act as a person enhancer to increase internal work motivation, but it may also serve to moderate the extent to which individuals are able to significantly influence a system. In addition, involvement and empowerment of all organizational members (including managers) in cooperative and collaborative (interactive) efforts to achieve quality improvements appear to be a key element to TQM. Results further reveal that world-class performance in operations (world-class company practices, operational excellence practices, and company non-financial performance) positively mediates the impact of critical factors of quality management practices on company financial performance. Results also point out that three out of six critical factors of quality management practices are positively associated with world-class company practices and operational excellence practices under the moderating of hierarchical level of managersâ abilities. World-class company practices and operational excellence practices have direct and significant effects on company non-financial performance. Furthermore, empirical results suggest that there is a positive and significant relationship between company non-financial performance and company financial performance.